Atherosclerotic Cardiovascular Disease - Pešek, Ksenija (IntechOpen, 2011)
Cardiovascular diseases (CVD) are still one of the leading causes of death in the world. The book Atherosclerotic Cardiovascular Disease is a contribution to the application of new knowledge in the area of cardiovascular diseases. The book comprises six chapters divided in three subsections, starting with the General Considerations of Cardiovascular Disease, through Diagnostic Techniques, and Specific Therapy.